Synthesis and in vitro Evaluation of 1, 2, 4‐Triazolo[1, 5‐a][1, 3, 5]triazine Derivatives as Thymidine Phosphorylase Inhibitors. (22nd August 2013) - Bera, Hriday; Dolzhenko, Anton V.; Sun, Lingyi; Dutta Gupta, Sayan; Chui, Wai‐Keung
Abstract : In our lead finding program, a series of 1, 2, 4‐triazolo[1, 5‐ a ][1, 3, 5]triazine derivatives were synthesized, and their in vitro thymidine phosphorylase inhibitory potential was explored. Among the different derivatives, compounds having keto group (C = O) at C7 and thioketo group (C = S) at C5 positions showed varying degrees of TP inhibitory activity comparable with positive control, 7‐deazaxanthine (7‐DX, 2 ) (IC50 value = 42.63 μm ). Enzyme inhibition kinetics study suggested that compoundIVn behaved as a mixed‐type inhibitor of the enzyme with respect to thymidine (dThd) as a variable substrate. CompoundIVn was also found to inhibit PMA‐induced MMP‐9 expression in MDA‐MB‐231 cells at sublethal concentrations. Computational docking study was performed to illustrate the enzyme inhibition kinetics and to explore the ligand–enzyme interactions. Abstract : CompoundIV n was identified as a lead among 21 derivatives of 1, 2, 4‐triazolo[1, 5‐ a ][1, 3, 5]triazines that were screened for inhibitory action against recombinant human thymidine phosphorylase (TP). CompoundIV n exhibited a mixed mode of inhibition towards TP and attenuated the MMP‐9 expression at sub‐lethal concentrations. The possible binding modes of the synthesized compounds with TP were also explored by molecular docking study.